O bildungsroman e a inexistência de um estado de direito no sertão rosiano de grande sertão: veredas - Silva, Andréia Paula da (2018)
Our studying proposal is to analyze the learning process played by Riobaldo, as a representative of the dispossessed class of material goods in a backward capitalist society. The favored ones use such dispossessed ones like base maintainer and sustentante of the social hierarchy, based on extreme inequalities. At the same time, it is known, historically, that these dispossessed have only three options of life: a) to accommodate themselves to poverty, living practically as semi-slaves; b) to believe, by religious means or by the bourgeois ideology of progress itself, in individual salvation or ascension; c) adhere to the resistance represented by jagunçagem (or cangaço, in the Northeast). Riobaldo's option for the third possibility entails an entire learning of a problematic hero or an anti-hero, in an inverted epic, constituting a formation process different from the prototype and of the conceptual configuration of Bildungsroman. This configuration is relativized by the Brazilian society, whose genesis includes negative aspects such as violence, force and authoritarian power.In this perspective, the main element of construction of Riobaldo is the suppression, represented by a sense of personal dissatisfaction and constant infinity.He searches for himself but never finds himself. He is always believed incomplete, in a sertanejo Brazil that, historically located in the republican period, that practically has no constitutional law or any public mechanism that characterizes a State of law. Thus, Riobaldo reaches old age and has the opportunity to complete his learning process through the remembrance of his history. Revisiting his past gives him the opportunity to complete his training. Temporal and spatial transformations reverberate significant changes in his cultural attitudes and lived experience. For this reason, we consider the old Riobaldo, now landowner, as the most complete version of his self. By recalling the long-lived facts, the farmer reflects his actions and seems to come to the end of his learning process, developing a consensus for the restlessness of a lifetime. In this context, scholars as Lukács; Bakhtin; Jr Folder (and his suppression theory); Mazzari and David Arrigucci bring profitable contributions to our approach. For all this, the present dissertation aims to contribute to the critical fortune of Grande Sertão: Veredas and to promote an interpretative investigation of academic pertinence on the implications contained in this work for the tendency of the Bildungsroman or novel of formation.